2010
DOI: 10.5380/ce.v15i3.18897
|View full text |Cite
|
Sign up to set email alerts
|

Supervisão De Enfermagem No Uso De Equipamento De Proteção Individual Em Um Hospital Geral

Abstract: Este artigo tem como objetivo descrever a supervisão de enfermagem em relação ao uso de Equipamentos de Proteção Individual (EPI), em hospital geral de município no interior paulista. O estudo teve cunho descritivo, sendo a população constituída por 20 enfermeiros, os quais responderam a um questionário. Para análise dos dados foi utilizada estatística descritiva. Os sujeitos, em sua maioria, são mulheres na faixa etária de 20-30 anos e trabalham há menos de três anos no hospital. Quanto ao EPI, 90% afirmam qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
0
7
0
17
Order By: Relevance
“…Of the 178 par cipants, there was a predominance of females, corrobora ng results of surveys have shown that women cons tute the largest con ngent of nursing workers (4,(11)(12) .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Of the 178 par cipants, there was a predominance of females, corrobora ng results of surveys have shown that women cons tute the largest con ngent of nursing workers (4,(11)(12) .…”
Section: Discussionmentioning
confidence: 59%
“…In work-related factors (N=178), the scores obtained were intermediate in both the Obstacles to Following the SP Scale (3.91) and in the Workload Scale (4,24 adherence to SP: discomfort using PPE, insuffi cient informa on, lack of me, and general beliefs of diffi cul es for following the SP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, continuing health education must be promoted, aiming to produce conscious attitudes and guarantee workers' protection. 32,33 Through continuing health education, researchers expect to obtain changes in work practice and technical and scientific knowledge about workers' health safety and promotion and disease prevention and the resulting patient safety. 34 Based on this context, health institution managements are expected to be committed to supporting professionals as they adhere to safe practices through continuing health education.…”
Section: Work Incidents With Nursing Teammentioning
confidence: 99%
“…Nurses performance in supervising the work of the nursing team happens through operative instruments used with the intention of optimizing actions of the groups in their work environment, and requires Skills and Attitudes to attain resolution with the institutional resources that are offered to them. [18][19][20] We highlight the importance of trained professionals in addressing and solving interpersonal, intergroup and institutional problems related to mobilizing the competence processes of change. Nurses need to seek cognitive and technical competencies, but also Behavioral and Attitude skills to innovate and sustain the transformations required in their managerial work in health.…”
mentioning
confidence: 99%